Mapping the Landscape of Chemo-Entrepreneurship in Indonesia: A Content Analysis and Research Trend Review - Ash Shiddiqi, Muhammad Habib; Adawiyah, Rabiatul; Purwaningsih, Dyah (Proceeding International Conference on Religion, Science and Education, 2026)
Chemo-Entrepreneurship (CEP) is an innovative approach in chemistry education that integrates mastery of scientific concepts with entrepreneurial skills to foster students’ critical, creative, and productive thinking abilities. This study aims to map the development and research trends related to CEP in Indonesia and to analyze the direction of chemistry learning model development that combines conceptual, practical, and economic value aspects in the teaching–learning process. The method employed is a Systematic Literature Review (SLR) combined with descriptive content and bibliometric analyses of 287 articles published during 2016–2023, analyzed following PRISMA guidelines and visualized using VOSviewer. The analysis results indicate a significant increase in publications since 2016, with a primary focus on learning outcomes, creative thinking skills, life skills, and entrepreneurial interest. The dominant research designs are experimental and Research and Development (R&D), oriented toward the development of modules, e-worksheets, and digital-based learning media applied to various chemistry topics such as colloidal systems, buffer solutions, acids and bases, and hydrocarbons. The review shows that CEP implementation can enhance students’ conceptual understanding, higher-order thinking skills, scientific creativity, and the ability to transform chemistry concepts into product innovations with economic value and social benefits. Moreover, CEP helps students understand the relationship between chemical theory and real-life production processes, thereby improving learning motivation and positive attitudes toward science. Nevertheless, studies on non-cognitive aspects, such as collaboration, scientific attitudes, and entrepreneurial character, remain limited, as do research employing mixed-method or longitudinal approaches. Research publications are still concentrated in a few major universities and predominantly in national journals, indicating the need to expand collaboration, diversify methodologies, and intensify international publications to strengthen CEP’s contribution to innovation in chemistry education in Indonesia.